2020
DOI: 10.1002/cpph.80
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Models for Studying the Impact of Macrophages on Cancer Cachexia

Abstract: Cancer‐associated cachexia is defined by loss of weight and muscle mass, and by the potential loss of adipose tissue accompanied by insulin resistance and increased resting energy expenditure. Cachexia is most prevalent in pancreatic cancer, the third leading cause of cancer‐related deaths. While various factors interact to induce cachexia, the precise mechanisms underlying this clinical condition are not fully understood. Clinically relevant animal models of cachexia are needed given the lack of standard diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Nixon et al suggested that SIK1 promotes insulin resistance on a high fat diet in skeletal muscle (Nixon et al, 2016 ). Insulin resistance plays an important role in many processes of muscular atrophy (Brener et al, 2020 ; Markov et al, 2020 ; Pár et al, 2021 ). Our study found that SIK1 expression was upregulated during denervation-induced muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Nixon et al suggested that SIK1 promotes insulin resistance on a high fat diet in skeletal muscle (Nixon et al, 2016 ). Insulin resistance plays an important role in many processes of muscular atrophy (Brener et al, 2020 ; Markov et al, 2020 ; Pár et al, 2021 ). Our study found that SIK1 expression was upregulated during denervation-induced muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…During differentiation, upon serum withdrawal from the culture medium and low concentration of horse serum cells can fuse forming multinucleated structures turning into elongated fibre-shaped myotubes [40]. As such, the cell line can be induced to undergo stepwise differentiation since a muscle precursor (satellite cells) to a myoblast, followed by a myocyte, and ultimately a multinucleated myotube [41]. These features enable the characterisation of the mechanisms that regulate each step of muscle development and functioning [41,42].…”
Section: C2c12 Cell Linementioning
confidence: 99%
“…As such, the cell line can be induced to undergo stepwise differentiation since a muscle precursor (satellite cells) to a myoblast, followed by a myocyte, and ultimately a multinucleated myotube [41]. These features enable the characterisation of the mechanisms that regulate each step of muscle development and functioning [41,42].…”
Section: C2c12 Cell Linementioning
confidence: 99%
“…The orthotopic animal model is histologically similar to PDAC patients, mimicking the TME associated with intact tumors, suggesting that the TME may be involved in cachexia induction. Studies in PDAC animal models have demonstrated that tumor-associated macrophages mediate muscle wasting via the activation of signal transducer and activator of transcription (STAT)3 signaling ( 134 , 141 ).…”
Section: Eolt Hypothesis In Pdac-ccmentioning
confidence: 99%